Psychiatric comorbidities and all-cause mortality in epilepsy: A nationwide cohort study - Puteikis, Kristijonas; Kazėnaitė, Edita; Mameniškienė, Rūta (Frontiers in Neurology, 2022)
Background People with epilepsy (PWE) having comorbid psychiatric conditions may be at greater risk of death. We aimed to determine the association between psychiatric disorders and all-cause mortality among PWE after adjustment for somatic comorbidities. Methods Based on data from the National Health Insurance Fund, a Cox survival analysis was done within a retrospective open cohort of all PWE (≥12 years) in Lithuania between January 2014 and June 2020. Cox models comparing mortality between PWE with or without psychiatric comorbidities were adjusted for sex, age, hospitalizations, and the epilepsy-specific comorbidity index. Results Of 47964 PWE (age Md=49, IQR=34-62 years, 60.3% male, follow-up Md=4.4 IQR=2.1-6.1 years), 10290 (21.5%) died during the study. The diagnosis of any psychiatric disorder (n=26137, 54.5%) was associated with increased mortality when adjusted for only sex and age (HR=1.13, 95% CI=1.09 to 1.18). After including the epilepsy-specific comorbidity index, the number of hospitalizations and hospital days in the analysis, only self-harm (HR=1.55, 95% CI=1.40 to 1.71) and substance use disorders (HR=1.39 95% CI=1.32 to 1.47), but not any psychiatric comorbidities (HR=0.92 95% CI=0.88 to 0.96) were related to elevated all-cause mortality. Mood, anxiety and behavioral disorders were associated with lower odds of mortality; however, they were rarely documented. Conclusions Our results suggest that psychiatric comorbidities increase all-cause mortality among PWE through their association with coexisting somatic conditions as only substance use disorders and self-harm were independently related to elevated all-cause mortality. Future clinical interview-based studies should explore the relationship between mortality in epilepsy and psychiatric comorbidities while adjusting for somatic comorbidities.